(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article analyzes abuse vocabulary based in fiction and newspaper texts. The conclusions about peculiarities of abuse vocabulary in fiction and newspaper materials are made. The importance of abuse vocabulary research is discussed. Specific features and prominence of abuse vocabulary are revealed by comparing abuse vocabulary in literary and newspaper texts. Precise arguments from literary and newspaper texts are given and analyze from an axilogical aspect. The situations of insulting the honor and reputation are investigated on the basis of judiciarylinguistic expertise. Alongside this, examples of abuse words of literary discourses are given, their usage and literary significance are revealed.